Performance Assessment of Critical Thinking: Conceptualization, Design, and Implementation - Braun, Henry I.; Shavelson, Richard J.; Zlatkin-Troitschanskaia, Olga; Borowiec, Katrina (Frontiers in Education, 2020)
Enhancing students’ critical thinking (CT) skills is an essential goal of higher education. This article presents a systematic approach to conceptualizing and measuring CT. CT generally comprises the following mental processes: identifying, evaluating, and analyzing a problem; interpreting information; synthesizing evidence; and reporting a conclusion. We further posit that CT also involves dealing with dilemmas involving ambiguity or conflicts among principles and contradictory information. We argue that performance assessment provides the most realistic—and most credible—approach to measuring CT. From this conceptualization and construct definition, we describe one possible framework for building performance assessments of CT with particular attention to extended performance tasks within the assessment system. The framework is a product of an ongoing, collaborative effort, the International Performance Assessment of Learning (iPAL). The framework comprises four main ingredients: (1) The storyline describes a carefully curated version of a complex, real-world situation. (2) A portfolio of documents in a range of formats, drawn from multiple sources chosen to have specific characteristics. (3) The challenge frames the task to be accomplished. (4) The scoring rubric which comprises a set of scales each linked to a facet of the construct. We discuss a number of use cases, as well as the challenges that arise with the use and valid interpretation of performance assessments. The final section presents elements of the iPAL research program that involve various refinements and extensions of the assessment framework, a number of empirical studies, along with linkages to current work in online reading and information processing.